Development a prototype of e-lbadah / Hasmawati Che Mat - Che Mat, Hasmawati (2006)
This project is present the 'Development a Prototype of e-lbadah' that focuses on providing information regarding theory and practice of Ibadah in Islam. The targeted users are villagers from Kampung Jenjarom, Kuala Langat. E-lbadah is one of the components of e-Village. This project using PHP as programming language, MYSQL as database and Apache as a web server. Joomla is a Content Management System (CMS) which allows anyone to create professional looking websites that can be updated and managed easily, without an in-depth knowledge of PHP scripting, MYSQL and web design. Prototyping is selected as the methodology in order to develop a prototype of e-lbadah. A prototype is an initial version of software which is used to demonstrate concepts, try out design options and generally to find out more about the problem and Its possible solution. This system is suitable if using prototype because rapid development of prototype. Result from the testing and experimental with the selected users is evaluated to see whether the user interface is adaptable with the user and resources available in the web portal easy access by the user. Suggestion and recommendation is also described to improve the development of e-ibadah.